If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2f + -1) = 6f + 5 Reorder the terms: 3(-1 + 2f) = 6f + 5 (-1 * 3 + 2f * 3) = 6f + 5 (-3 + 6f) = 6f + 5 Reorder the terms: -3 + 6f = 5 + 6f Add '-6f' to each side of the equation. -3 + 6f + -6f = 5 + 6f + -6f Combine like terms: 6f + -6f = 0 -3 + 0 = 5 + 6f + -6f -3 = 5 + 6f + -6f Combine like terms: 6f + -6f = 0 -3 = 5 + 0 -3 = 5 Solving -3 = 5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8(4-s)+s=8+s | | 4x+10=80 | | 7(7-3r)=-r-11 | | 7(7-3r)=-r-121 | | -6m+7=7m+10 | | .125v=.25 | | 8x+1=0 | | -12-17=-89 | | 4y-5+y+51=8y+50-5y | | (2x^3y^4)5= | | .66x=-8 | | (y^4)2= | | (-2x^3y^2)(-3x^2z^2)(-5y^3z^3)= | | 4(2x+7)-6(4x-8)=12x+3(4x-9) | | (-x^2y^3z)(-x^3y^4)= | | (x^2y^4)(xy^7)= | | y-11y= | | 7(-6)+3(-5)= | | (7c^2)(-6c^4)= | | x^4-30x^2-125=0 | | slopey=4x+5 | | 91/4+(-43/3)= | | x^4-30x^2+115= | | s(x+t)=tx-m | | (y^2+4y)-(y^2+10y)= | | (x^2-3xy)-(-2x^2+xy)= | | 2c-8= | | 1-3x=10x-20 | | 4(y+1)-3-5y=2(y-2) | | x+(12-x)=38 | | 4x^3=36 | | -19+8x=x-40 |